Defect-dependent colossal negative thermal expansion in UiO-66(Hf) metal–organic framework1. Issue 17 (7th May 2015) - Cliffe, Matthew J.; Hill, Joshua A.; Murray, Claire A.; Coudert, François-Xavier; Goodwin, Andrew L.
<x xml:space="preserve">Abstract</x> Thermally densified UiO-66(Hf) shows the strongest reported isotropic negative thermal expansion (NTE) in a metal–organic framework. Incorporation of defects allows for tuning of the magnitude of both the densification and the NTE.